Business, Human Rights and the Environment—Using Macro Legal Analysis to Develop a Legal Framework That Coherently Addresses the Root Causes of Corporate Human Rights Violations and Environmental Degradation - Stephen J. Turner (MDPI AG, 2021)
This article applies ‘macro’ legal analysis to the challenge of legal reform related to corporate responsibility for human rights violations and degradation of the environment. It recognises that the approaches from different communities of lawyers to the negative impacts on human rights and the environment caused by companies, sometimes operate in isolation from each other, are not always mutually supportive, can lead to a fragmentation of effort, and may not address the root causes of the problem. In particular, this article analyses the extent to which existing approaches tend to address symptoms of the issues, rather than the root causes themselves. It makes the case that in this regard specific root causes exist within the frameworks of corporate law in all jurisdictions and various aspects of international economic law too. To carry out the study, it employs macro legal analysis, a methodology not previously applied in this field, as a means of developing an understanding of the legal frameworks that, it argues, influence corporate decision making that can affect human rights and the environment. It undertakes an analysis that incorporates relevant corporate law, World Trade Organisation (WTO) law, international investment law, the law relating to multilateral development banks (MDBs), and international insurance law. By using this form of anlaysis it is possible to show how legal frameworks can operate in unison, reinforcing each other providing a cumulative effect that can influence corporate decision makers. Finally, based on the results of the analysis, it suggests a possible strategy of macro-level reforms that could be applied to the re-design of relevant legal frameworks to better facilitate the full protection of human rights and to achieve net zero degradation of the environment. As a result it seeks to demonstrate how this approach can be strategically applied by both human rights and environmental lawyers as a common pathway towards effective legal reform.